ELN gene triplication responsible for familial supravalvular aortic aneurysm. (17th June 2014) - Guemann, Anne-Sophie; Andrieux, Joris; Petit, Florence; Halimi, Emmanuel; Bouquillon, Sonia; Manouvrier-Hanu, Sylvie; Van De Kamp, Jiddeke; Boileau, Catherine; Hanna, Nadine; Jondeau, Guillaume; Vaksmann, Guy; Houfflin-Debarge, Veronique; et al.
Abstract Supravalvular aortic aneurysms are less frequent than abdominal ones. Among Supravalvular aortic aneurysm aetiologies, we focused on dystrophic lesions as they can be secondary to genetic causes such as elastin anomaly. We report on a familial 7q11.23 triplication – including the ELN gene – segregating with a supravalvular aortic aneurysm. During her first pregnancy, our index patient was diagnosed with tuberous sclerosis and with a Supravalvular aortic aneurysm. The foetus was affected equally. For the second pregnancy, parents applied for preimplantation diagnosis, and a subsequent prenatal diagnosis was offered to the couple, comprising TSC1 molecular analysis, karyotype, and multiplex ligation probe amplification. TSC1 mutation was not found on foetal deoxyribo nucleic acid. Foetal karyotype was normal, but multiplex ligation probe amplification detected a 7q11.23 duplication. Quantitative-polymerase chain reaction and array-comparative genomic hybridisation carried out to further assess this chromosome imbalance subsequently identified a 7q11.23 triplication involving ELN and LIMK1. Foetal heart ultrasound identified a Supravalvular aortic aneurysm. A familial screening was offered for the 7q11.23 triplication and, when found, heart ultrasound was performed. The triplication was diagnosed in our index case as well as in her first child. Of the 17 individuals from this family, 11 have the triplication. Of the 11 individuals with the triplication, 10 were identified to have a supravalvular aortic aneurysm. Of them, two individuals received a medical treatment and one individual needed surgery. We provide evidence of supravalvular aortic aneurysm segregating with 7q11.23 triplication in this family. We would therefore recommend cardiac surveillance for individuals with 7q11.23 triplication. It would also be interesting to offer a quantitative-polymerase chain reaction or an array-comparative genomic hybridisation to a larger cohort of patients presenting with isolated supravalvular aortic aneurysm, as it may provide further information.